PENGUATAN MASYARAKAT MADANI MELALUI DAKWAH KEWARGAAN - Muhammad Sulthon (Millah: Journal of Religious Studies, 2013)
By the end of the caliphate system, the Islamic world face many questions, among others, the question of the relationship of Muslims as citizens of the country. A t the time of the new order, the majority of Muslims as citizens of the nation-state in Indonesia do not have bargaining power significant in balancing the country's dominance. This relationship is not conducive to the process of democratization. To overcome it appears some ikhtiar, among citizenry missionary movement to create a civil society. Missionary citizenship can be done by internalization Islamic values relevant to the citizens of the community.